2016
DOI: 10.21608/eajbsa.2016.12779
|View full text |Cite
|
Sign up to set email alerts
|

Life History of the Predaceous Mite Cunaxa capreolus (Berlese) (Acari: Prostigmata: Cunaxidae) When Fed on Different Diets at Different Temperatures

Abstract: This work aimed to study different biological aspects of the predatory mite, Cunaxa capreolus (Berlese) when fed on different diets mainly free living nematode, Rhabditis scanica Allgen and Entomobrya musatica Stach (Collembola) at 25 and 35+2 °C and relative humidity 75+5% R.H. in laboratory From the study, it was obvious that the different biological aspects (incubation period, life cycle, longevity and life span) of the predator were significantly affected by feeding on the different diets. When the two pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Comparison of the effect of a nematode-based diet and other diets on mite fitness has only been conducted for Cunaxa capreolus (Berlese) and Pulaeus pseudominutus (Shiba). The fecundity of C. capreolus was higher when feeding on J2 of M. incognita than when feeding on J2 of Tylenchulus semipenetrans Cobb [120] and was higher when feeding on the colembolan Entomobrya musatica Stach than on the nematode Mesorhabditis scanica (Allgén) Sudhaus (cited as Rhabditis scanica Allgén) [119]. In the case of P. pseudominutus, no differences in fecundity were observed when mites were fed with the fungi Fusarium oxysporum Schltdl.…”
Section: Prostigmatamentioning
confidence: 95%
See 1 more Smart Citation
“…Comparison of the effect of a nematode-based diet and other diets on mite fitness has only been conducted for Cunaxa capreolus (Berlese) and Pulaeus pseudominutus (Shiba). The fecundity of C. capreolus was higher when feeding on J2 of M. incognita than when feeding on J2 of Tylenchulus semipenetrans Cobb [120] and was higher when feeding on the colembolan Entomobrya musatica Stach than on the nematode Mesorhabditis scanica (Allgén) Sudhaus (cited as Rhabditis scanica Allgén) [119]. In the case of P. pseudominutus, no differences in fecundity were observed when mites were fed with the fungi Fusarium oxysporum Schltdl.…”
Section: Prostigmatamentioning
confidence: 95%
“…More studies have been performed, but the results show that this mite group does not seem to have a nematophagous habit for the most part. A total of 16 species, mainly of the family Cunaxidae, are reported to consume nematodes, with most able to be reared or developed on nematode-based diets [116][117][118][119][120]. Walter [7] found that several species of Eupodidae are capable of feeding on nematodes, but at low frequency and with a preference for microphytes.…”
Section: Prostigmatamentioning
confidence: 99%